Determinación de hemoglobina, hematocrito y riesgo de anemia en personas adultas que pertenecen a la iglesia central adventista de la ciudad de Trujillo, abril, 2013 - Angeles Aguirre, Luisa Milagros Liszet (2013)
Serum levels were determined Hemoglobin and Hematocrit in 78 adults of both sexes belonging to the Adventist Central Church of the city of Trujillo. Taking place spreading activity through posters indicating the determinations to be made, time, date, place and same them to come fasting. Performing a talk prior to sampling motivating their participation for the assessments. Filling requesting informed consent also distributing leaflets, using a survey to collect information on personal data, vital signs, nutritional aspect, socioeconomic, lifestyle and health, in the same way we applied a test to measure the risk Anemia possibly people are exposed. 78 Blood samples were processed according to the method for each determination, 72% of males and 68% females have normal hemoglobin value, 28% and 32% in value respectively, and 60% male female and 57% have normal hematocrit, 32% and 28% respectively low value, also 8% and 15% higher values. The results were subjected to nonparametric tests of independence of criteria using the Chi-Square distribution and the Pearson correlation coefficient. Proving the existence of relationship between hemoglobin and hematocrit. According to tests measuring risk for anemia and surveys the percentage of people at high risk is lower with a value of 7.69%, while the low risk significantly predominates in 46.15%, with a population that has largely with a good diet and healthy lifestyle